Two-Dimensional Code Based Spatiotemporal Modeling and Its Application in Object Tracing. (30th August 2015) - Gao, Yanghua; Zhang, Zhihua; Wang, Huanwen; Lu, Hailiang
Space-time consistency is of great importance for mapping things from physical world to cyber world, which could be one of the fundamental issues in constructing cyber-physical system (CPS). A two-dimensional code spatiotemporal modeling method is proposed in this paper. We apply the two-dimensional code as an information carrier to store object's characteristics (object's ID, attributes, instructions, spatiotemporal data, etc.), the smartphone as a mobile device to obtain the object's real-time spatiotemporal data with its system time and GPS module; then the object's spatiotemporal information can be transmitted and stored in a backend server with a database. Meanwhile, the object's spatiotemporal information can also be inquired by smartphone users and other web users. A use case that applied this proposed method to trace object's smartphone information is described later, and the result shows that tracing objects with two-dimensional code has many advantages, such as fast reading and transmitting, low cost, and robust, confidential, and strong readability; furthermore, the proposed modeling method keeps the consistency of object's time and space in CPS.